INHIBITION OF THE ISOLATED GUINEA-PIG URINARY BLADDER CONTRACTIONS BY SILDENAFIL (VIAGRA®): IN VITRO STUDY - Onur, Rahmi; Orhan, Irfan; Semercioz, Atilla; Ayar, Ahmet (Aves, 2005)
Introduction: Overactive bladder is a medical condition which is characterized by an overactive detrusor, involuntary contractions and/or incontinence. This condition is usually treated medically with anticholinergics being the medication of choice in most cases. Recently, different pharmacological alternatives have been defined in the treatment of detrusor instability. Among these, phosphodiesterases which play important roles in the regulation of smooth muscle tone have been investigated in various clinical and experimental studies. In the present study, we aimed to evaluate the effects of sildenafil (Viagra (R)) on the agonist induced contractility of isolated Guinea-pig bladder. Materials and Methods: A total of 10 adult Guinea-pigs weighing 400-450 gr were decapitated. Using a midline abdominal incision the bladder was found, kept intact and isolated from the surrounding tissues. All bladders were first placed into the saline solution and the strips were prepared. A 10x2 mm of isolated guinea-pig bladder strip was prepared and placed into a jacketed organ bath containing physiological solution. A passive tension of 1 gr was maintained. After the equilibration period acetylcholine (Ach) (10 mu M), a strong agonist, was added into the medium and the contractions were recorded. Following the contractions, sildenafil (Viagra (R)) was added into the organ bath. Amplitude and frequency of contractions and area under the contraction curves were evaluated by 10-min intervals. Results: During equilibration period, small amplitude contractions were noted. After addition of ACh into the jacketed organ bath which contains physiological saline solution, contractions with higher amplitude were observed. Mean amplitude of contractions in isolated bladder strips after Ach was 1.81 g (+/- 0.31 SEM). Application of 0.5mM Sildenafil significantly reduced the mean amplitude of contractions and it was recorded as 0.76 g (+/- 0.15 SEM). Similarly, use of sildenafil also reduced the frequency of contractions. Conclusion: Urge urinary incontinence is the most common form of urinary incontinence. Antimuscarinic agents are widely used in the treatment of urgency and/or incontinence. However, they did not reach enough efficacies because of their frequent side effects. In the present study, we investigated the efficacy of sildenafil on pre-contracted isolated Guinea-pig bladder and determined that sildenafil significantly decreased both the amplitude and the frequency of bladder contractions. The results of our study support the hypothesis that phosphodiesterase inhibitors can be potentially helpful in the regulation of smooth muscle tone in various tissues. However, there is need for further studies to reveal the exact roles of sildenafil and other phosphodiesterase inhibitors in the treatment of overactive bladder.
Keywords: Bladder; guinea-pig; contraction; sildenafil; inhibition